PENYAKIT LAYU FUSARIUM (Fusarium oxysporum f.sp. cubense (E.F.Smith) Synd. & Hans.) PADA TANAMAN PISANG (Musa spp.) DAN HUBUNGANNYA DENGAN KEBERADAAN NEMATODA Radopholus similis DI LAPANGAN - Friska Erawati Sitepu; Lisnawita Lisnawita; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2014)
Fusarium wilt (Fusarium oxysporum f.sp. cubense (E.F.Smith) Synd. & Hans.) (Foc) on banana(Musa spp.) and its related with Radopholus similis in the Field. This research aims to knowrelationships between R. similis with fusarium wilt in the field. This research was conducted byusing survey method. Samples were taken from Kampung Susuk, Pancing and Sari Rejo in Medandistrict. Tanjung Slamat and Sibiru-biru in Deli Serdang district. Marjanji Pisang, Mekarsari andSimpang Raya in Simalungun district. The result showed that the highest disease incident found atSibiru-biru village Deli Serdang districk (64.45%), R.similis populations was 28,7 and the numberof fusarium propaguls was 354. Meanhwile, the lowest disease incident found at Simpang RayaSimalingun district (10%), R.similis populations was 7,4 and the number of fusarium propagulswas 82. Fusarium oxysporum f.sp. cubense has positive corelation with R.similis in fields.Keywords: Fusarium oxysporum f.sp. cubense, Radopholus similis, banana